The transferability of the western management tradition to the non-western public service sectors an East African perspective - Moris, Jon R. (1976)
Development projects and activities undertaken in Africa and in most other Third or "Fourth World" countries which involve the transfer and application of western management techniques have often failed to produce the expected results. The article explores possible causes, explanations and conditions which impede or facilitate the transfer of western management practices to East Africa in particular and other Asian countries in general. Administrative "rationality" and "irrationality" are discussed in- Western and Fourth World cultural contexts, giving emphasis on the need to understand how the latter's administrative systems actually work before western managerial practices could be transferred effectively.
Keywords: Public administration -- Africa; Public administration -- Research; Personnel management; Management -- Social aspects